Carbon Assimilation by the Picoplanktonic Community Inhabiting the Secondary Chlorophyll Maximum of the Anoxic Marine Zones of the Eastern Tropical North and South Pacific - Aldunate, Montserrat; von Dassow, Peter; Vargas, Cristian A.; Ulloa, Osvaldo (Frontiers in Marine Science, 2022)
Anoxic marine zones (AMZs) constitute pelagic systems distinguished from the oxygen minimum zones (OMZs) by the complete absence of detectable oxygen and the accumulation of nitrite in mid-waters. At the top of the oxygen-depleted layer and below the oxycline, nutrients are abundant; light intensity is very much reduced (<1% of incident light) and a secondary chlorophyll maximum (SCM) is developed. The shoaling of the oxygen-depleted layer, product of the AMZ expansion, could enhance this SCM, which has little-known biogeochemical effects. Here, we show that the SCM is contributing a measurable signal in the particulate organic carbon (POC), enough to alter the δ13CPOC in the top of the oxygen-depleted layer. This data showed significant differences among stations with and without the development of a SCM, being 3.0‰ heavier when a SCM is developed, and indicating photosynthetic activity and/or remineralization in the top of the AMZ. More depleted δ13CPOC values were also found when no SCM was present indicating stronger chemoautotrophic activity, potentially driven by anammox and sulfur-oxidizing bacteria activity. Assimilation rate data show that when sufficient light and Prochlorococcus are present, photosynthesis exceeds chemoautotrophic carbon fixation, and can exceed heterotrophic assimilation of glucose or acetate. However, in the majority of the stations, assimilation rates of both glucose and acetate exceeded carbon fixation rates under light stimulation, suggesting that often the SCM is still a net heterotrophic system.